Becket. - Glenville, Peter, 1913-1996.; Olivier, Laurence, 1907-1989.; Quinn, Anthony, 1915-2001.; Powers, Marie, 1910-1973.; Anouilh, Jean, 1910-1987.; Motley (Organization); St. James Theatre (Organization : New York, N.Y.); Richard L. Coe Theater Programs Collection (Library of Congress) (1960)
St. James Theatre, David Merrick presents Laurence Olivier, Anthony Quinn, in Peter Glenville's production of "Becket," by Jean Anouilh, translated by Lucienne Hill with Marie Powers, production designed by Oliver Smith, lighting by Jean Rosenthal, costumes by Motley, music by Laurence Rosenthal, directedby Mr. Glenville.
St. James Theatre, premiere October 5, 1960.
Cast: Anthony Quinn, Robert Duke, Laurence Olivier, Sydney Walker, Will Hussung, Earl Montgomery, Victor Thorley, Robert Weil, Hilary Beckett, Tom Leith, Dran Seitz, Louis Zorich, Ronald Weyand, Mel Berger, Ferdi Hoffman, Madeline Morgan, Claude Woolman, Brian Crowe, Dino Terranova, Peter De Firis, Julian Miller, Marie Powers, Margaret Hall, Dennis Rosa, Kit Culkin, Robert Eckles, Edward Atienza, Sydney Walker.
Title devised by Library staff.
"Playbill. Vol. 4, October 17, 1960, No. 43"--p. 5.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Theater programs -- New York (State) -- New York; Theater programs -- 1960.